EFFECT OF MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF EDUCATION AND CULTURE MUSI RAWAS NORTH - AD. Oktarianda; Noorchamid Ustadi (Jurnal Interprof, 2017)
This research was conducted at the Department of Education and Culture Musi Rawas North with the aim to determine the effect of motivation and organizational culture on employee performance partially and simultaneously, the analysis usedin this research is multiple linear regression coefficient determination test, F test and t test , samples used in this study were all employees of the Department of Education and Culture Musi Rawas North. Then the regression coefficient value b2 = 0680 this means an increase of one unit every variable of organizational culture will happen improve employee performance by 0.680 units of coefficient of determination Ghozali (2005: 83) states that this test is performed to measure the ability of the model in explaining the variance of the dependent variable. With the formula used Suliyanto (2011: 59). From the calculation of the coefficient of determination above, it can be seen that the value of R Square is 0.588, which means that the influence of motivation and organizational culture on employee performance amounted to 58.8% while the remaining 41.2% influenced by other factors such as labor discipline, competence, supervision and others that are not included in penelitian.Uji F assisted with SPSS 17. Sugiyono (2010: 286) to test the coefficient together - together toward regression test was used F. obtained value Fhitung 62.131dan Ftable obtained from: Ftabel = n - m - 1 = 90-2-1 = 87 (seen in table 80 is equal to 3,238 F). Ftabel for 3238 shows that the F count> F table means that Ho is rejected and Ha accepted. This means that there is the influence of organizational culture on the motivation and performance of employees at the Department of Education and on culture Musi Rawas North. Effect of Motivation on Employee Performance at the Department of Education and Culture Musi Rawas North. Advanced testing is a significant test of functioning if researchers want to find the meaning of the relationship of variable X to Y then the correlation results PP <that can be tested significantly. Retrieved tcount of 5224 and ttabel obtained table = n - m - 1 = 90-2-1 = 87 (seen in Table 80 amounted to 1,671 t). ttable of 1671 shows that F count> F table means that Ho is rejected and Ha accepted. This means that there is the influence of motivation on the performance of employees at the Department of Education and on culture Musi Rawas North. Influence of Organizational Culture on Employee Performance at the Department of Education and Culture Musi Rawas North. Advanced testing is a significant test of functioning if researchers want to find the meaning of the relationship of variable X to Y then the correlation results PP <that can be tested significantly. Retrieved tcount of 10 315 and ttabel obtained table = n - m - 1 = 90-2-1 = 87 (seen in Table 80 amounted to 1,671 t) ttable of 1671 shows that F count> F table means that Ho is rejected and Ha accepted , This means that there is the influence of organizational culture on the performance of employees at the Department of Education and on culture Musi Rawas North.